C.-A. Sainte-Beuve : Chateaubriand et son groupe littéraire sous l'empire - Uffenbeck, Lorin A. (Studies in the Romance languages and literatures, 2019)
Based on contemporary sources and recent authoritative scholarship, this analytical index brings together in concise form the available information concerning each of the persons and works named or alluded to in Sainte-Beuve's most-discussed book. The introduction, index, notes, and appendices are in French.